Longitudinal patterns of inflammatory mediators after acute HIV infection correlate to intact and total reservoir - De Clercq, Jozefien; De Scheerder, Marie-Angélique; Mortier, Virginie; Verhofstede, Chris; Vandecasteele, Stefaan J.; Allard, Sabine D.; Necsoi, Coca; De Wit, Stéphane; Gerlo, Sarah; Vandekerckhove, Linos (Frontiers in Immunology, 2024)
Background Despite the beneficial effects of antiretroviral therapy (ART) initiation during acute HIV infection (AHI), residual immune activation remains a hallmark of treated HIV infection. Methods Plasma concentrations of 40 mediators were measured longitudinally in 39 early treated participants of a Belgian AHI cohort (HIV+) and in 21 HIV-negative controls (HIV-). We investigated the association of the inflammatory profile with clinical presentation, plasma viral load, immunological parameters, and in-depth characterization of the HIV reservoir. Results While levels of most soluble mediators normalized with suppressive ART, we demonstrated the persistence of a pro-inflammatory signature in early treated HIV+ participants in comparison to HIV- controls. Examination of these mediators demonstrated a correlation with their levels during AHI, which seemed to be viremia-driven, and suggested involvement of an activated myeloid compartment, IFN-γ-signaling, and inflammasome-related pathways. Interestingly, some of these pro-inflammatory mediators correlated with a larger reservoir size and slower reservoir decay. In contrast, we also identified soluble mediators which were associated with favorable effects on immunovirological outcomes and reservoir, both during and after AHI. Conclusion These data highlight how the persistent pro-inflammatory profile observed in early ART treated individuals is shaped during AHI and is intertwined with viral dynamics